A primary study on rat fetal development and brain-derived neurotrophic factor levels under the control of electromagnetic fields - Sima DastAmooz; Shahzad Tahmasebi Broujeni; Nahid Sarahian (AOSIS, 2023)
Background. In previous researches, electromagnetic fields have been shown to adversely affect the behavior and biology of humans and animals; however, body growth and brain-derived neurotrophic factor levels were not evaluated. Objective. The original investigation aimed to examine whether Electromagnetic Fields (EMF) exposure had adverse effects on spatial learning and motor function in rats and if physical activity could diminish the damaging effects of EMF exposure. In this study, we measured anthropometric measurements and brain-derived neurotrophic factor (BDNF) levels in pregnant rats' offspring to determine if Wi-Fi EMF also affected their growth. These data we report for the first time in this publication. Methods. Twenty Albino-Wistar pregnant rats were divided randomly into EMF and control (CON) groups, and after delivery, 12 male fetuses were randomly selected. For assessing the body growth change of offspring beginning at delivery, then at 21 postnatal days, and finally at 56 post-natal days, the crown-rump length of the body was assessed using a digital caliper. Examining BDNF factor levels, an Enzyme-linked immunosorbent assay ELISA kit was taken. Bodyweight was recorded by digital scale. Results. Outcomes of the anthropometric measurements demonstrated that EMF blocked body growth in rats exposed to EMF. The results of the BDNF test illustrated that the BDNF in the EMF liter group was remarkably decreased compared to the CON group. The results indicate that EMF exposure could affect BDNF levels and harm body growth in pregnant rats' offspring. Conclusions. The results suggest that EMF exposure could affect BDNF levels and impair body growth in pregnant rats' offspring.